Comprehensive exploration of the adsorption capacity of innovative betaine-based deep eutectic solvents for carbon dioxide capture. (March 2023) - He, Nan; Chen, Qicheng; Fan, Jing; Song, Fenhong; Zhang, Yukun; Mu, Han
Highlights: Synthesized innovative and efficient halogen-free betaine-based deep eutectic solvents to capture CO2 . Revealed effect of temperature, pressure and concentration on adsorption capacity of DESs for CO2 . Established experimental correlation and predicted accurately adsorption capacity of DESs for CO2 . Obtained the Henry's constant and thermodynamic parameters of innovative DESs. Abstract: Compared with traditional organic solvents and ionic liquids, deep eutectic solvents (DESs) as innovative emerging solvents has attracted widespread attentions in the field of CO2 absorption due to its remarkable advantages, such as low melting point, cheapness, easy preparation, regeneration and biodegradation. Herein the halogen-free DESs constituting of betaine as hydrogen bond acceptor, 1, 2-propanediol and diethylene glycol as hydrogen bond donor were employed to absorb CO2 . The CO2 absorption capacity of DESs with different molar ratios was measured at a certain temperature (303.15–348.15 K) and pressure (180–770 kPa). The results show that the solubility of CO2 in DESs can be improved by decreasing the temperature and increasing the pressure. The solubility of CO2 in DESs increases with increasing mole ratio of 1, 2-propanediol, but decreases with increasing mole ratio of diethylene glycol. The Jou and Mather model was used to calculate the CO2 solubility data, which was compared with the experimental results. Through the estimated Henry's constant, the gibbs free energy, enthalpy and entropy of absorption were calculated and the results indicate that the CO2 dissolution in DESs is a non-spontaneous exothermic process. Regeneration can be achieved by depressurizing and heating the DES-CO2 system. By comparing with the Henry's constant Hm of the reported solvents, this work provides the possibility and space for further optimizing the use of new materials DESs to capture CO2 .